Validation of scale of assessment of significance of caring - Rosa Aparecida Pavan Bison; Debora Vieira Almeida; Jair Licio Ferreira Santos; Antonia Regina Ferreira Furegato (Universidad de Alicante, 2014)
Following Morse benchmark, the Scale for the Assessment of Significance of Care (SASC) received a construct validation in 2003. This present paper aimed to continue the process of validation of the instrument by assessing its internal consistency and reproducibility. To estimate internal consistency it was used the original 2003 information to calculate the values of Cronbach's Alpha in each of the five areas and for each question. Appraisal of Reproducibility was done through test-retest technique: the scale was administered to 98 subjects, all student nurses. The reproducibility was measured by the degree of agreement between the two measurements using the percentage of observed agreement, the intraclass correlation coefficient and the coefficient of reliability of Spearman-Brown. It was concluded that it is a consistent instrument with good reproducibility that can contribute to the knowledge of the attitudes of nurses in relation to care.